Part II. The feeding ecology of local Mallard and other wildfowl - Olney, P J S (Wildfowl, 1967)
The feeding habis of Mallard Anas p. platyrhynchos in an area near Sevenoaks, Kent, were investigated by 226 stomach analyses and by observations between 1957 and 1965. The main feeding areas included the river and its banks, the wet meadows by the river, the gravel pits and their margins and beneath oak trees Quercus robur in the valley. The dorminant plants in these areas are described. The food taken varied each year, depending on the production and availability of food items, which were correlated with changes in the habitat (e.g. river clearance, grazing) and with the effects of differing weather conditions (e.g. flooding, dry summers). The most frequently taken foods were: in the river, the leaf and stem of water crowfoot Ranunculus aguatilis, together with the mollusc Hydrobia jenkinsi and the caddie fly Hydropsyche angustipennis, and to a lesser extent the seeds of flote-grass Glyceria fluitans; from the river banks, the seeds of bur-reed Sparganium erectum and water-pepper Polygonum hydropiper; from the wet meadows, the seeds of creeping buttercup Ranunculus repens, persicaria Polygonum persicaria, hammer sedge Carex hirta and sharp dock Rumex conglomeratus; in and around the gravel pits a wide variety, mainly the seeds of alder Alnus glutinosa, various Polygonum species, S. erectum and parts of horsetail Equisetum, as well as Chironomidae and Hydropsyche lamrae. Acorns were eaten in the years when oaks produced seed. Forty other wildfowl were collected and their stomach contents were analysed. They included Teal Anas c. crecca, Wigeon A. penelope, Tufted Duck Aythya fuligula, Pochard A. ferina, Smew Mergus albellus, White-fronted Geese Anser a. albifrons and Canada Geese Branta canadensis.